PENGEMBANGAN PENDEKATAN OPEN-ENDED DALAM PEMBELAJARAN IPS UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR TINGKAT TINGGI SISWA SEKOLAH DASAR DI KALIMANTAN UTARA - Ahsan Sofyan; Disman Disman; Kokom K; Erlina W (Universitas Borneo Tarakan, 2019)
Abstract: The application of the Open-ended approach in the social studies learning process can develop high-level thinking skills ofelementary school students. The formulation of the problem in this studyis how to develop, implement and influence and impact the applicationof the Open-Ended learning model in social studies learning to improvethe high-level thinking skills of elementary school students. The methodused is the research and development (R D) of Borg and Gall. Theresearch locations were ten elementary schools in five districts/cities inNorth Kalimantan. The subjects of this study were high-class teachersand students (grades 4.5, and 6) using purposive sampling techniques.The results showed that the Open-Ended learning model was feasible touse based on peer evaluations, expert lecturers, and effective teacherscould improve the high-level thinking skills of students in ElementarySchool seen from the application of the Open-Ended learning model inthe learning process when the experiment class students were morehigher than control class students. In the final model validation test,where the average experimental class post-test was 83.33 higher thanthe control class, which obtained an average of 80.07.Keywords: Open-Ended Approach; Social Studies Learning; High-LevelThinking Ability